2008
DOI: 10.1097/mnm.0b013e3282f813a4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of whole-body metabolic burden as a quantitative measure of disease activity in lymphoma: a novel approach with fluorodeoxyglucose-PET

Abstract: The results of this analysis demonstrate that measurement of WBMB may prove to be superior to the existing methods in assessing and managing patients with non-Hodgkin's lymphoma. This index may be the best way to monitor the changes in WBMB as a patient is undergoing treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 17 publications
0
43
1
Order By: Relevance
“…Particularly not when considering that most malignant tumours are heterogeneous, and thus for this reason alone SUVmax is not a reliable measure of any of these characteristics. Therefore, assessment approaches taking this into account have been proposed, including estimating the "whole-body metabolic burden" or "total lesion glycolysis" [9,10]. The extent of disease, reflected by its stage, is considered one of the most important predictors of outcome in almost any type of lymphoma, and thus may serve as a guide for therapy.…”
mentioning
confidence: 99%
“…Particularly not when considering that most malignant tumours are heterogeneous, and thus for this reason alone SUVmax is not a reliable measure of any of these characteristics. Therefore, assessment approaches taking this into account have been proposed, including estimating the "whole-body metabolic burden" or "total lesion glycolysis" [9,10]. The extent of disease, reflected by its stage, is considered one of the most important predictors of outcome in almost any type of lymphoma, and thus may serve as a guide for therapy.…”
mentioning
confidence: 99%
“…Previous studies performed in patients with a variety of different neoplastic diseases-such as head and neck cancer (7,8), lung cancer (9,10), pleural mesothelioma (11), pharyngeal cancer (12), thyroid cancer (13), non-Hodgkin lymphoma (14,15), osteosarcoma (16,17), and soft-tissue sarcoma (18)-showed that 18 F-FDG PET/CT, by determining the uptake and volume of metabolic active lesions in the whole body, allows direct measurement of metabolic tumor burden. In MM, therefore, metabolic tumor burden measured by 18 F-FDG PET/CT may reflect plasma cell mass throughout the bone marrow in the whole body, thus providing a novel potential prognostic factor.…”
mentioning
confidence: 99%
“…The maximum standardized uptake value (SUVmax) has been used in daily clinical setting to evaluate the degree of malignancy, www.intechopen.com metabolic response to therapy, and early detection of disease recurrence (Ngeow JY et al, 2009;Schoder H et al, 2005;Spaepen K et al, 2002;. Measurements of metabolic burden, which incorporate both FDG uptake and PET lesion volume may prove more useful for risk stratification and response assessment (Berkowitz A et al, 2008).…”
Section: Fdg-petmentioning
confidence: 99%